(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The institutional theory elucidates that businesses seek to provide a reasonable and relevant explanation for their behaviour because they are motivated by the need for social justification within institutional settings that shape their strategic directions and decisions. This study examined the supply chain performance implications of institutional pressures and supply chain technology among Ghanaian firms. The study employed the quantitative method and survey design. Data was sourced from 394 managers of small to large-scale firms operating in the Greater Accra Metropolis of Ghana. Data were analysed using Structural Equation Models (SEM). The study found that institutional pressures positively relate to supply chain performance. It was also discovered that supply chain technology utilisation (SCTU) mediates the relationship between Institutional pressures (INP) and supply chain performance (SCP). The finding shows the relative importance of INP and SCTU on the performance of supply chains of firms in Ghana. The study recommended that firms in Ghana and Africa must pay critical attention to supply chain technology to enhance their supply chain operations. The study provides practical implications for firms by highlighting the importance of institutional pressures and supply chain technology utilization in supply chain performance. This will provide firms with the insight to identify the most important institutional pressures that affect their supply chain technology utilization and performance. The study also encourages the use of technology in supply chain management. This can lead to more efficient and effective supply chains, which can help society by lowering prices and making more products available. The study is unique in its focus as it attempts to shift the discourse beyond how institutional pressures influence firms’ environmental and sustainability performance to how they impact supply chain performance.